Role of gut microbiota and inflammatory factors in acute respiratory distress syndrome: a Mendelian randomization analysis - Ma, Jiawei; Zhu, Zigang; Yishajiang, Yisikandeer; Alarjani, Khaloud Mohammed; Hong, Lei; Luo, Liang (Frontiers in Microbiology, 2023)
Background: Acute respiratory distress syndrome (ARDS) is a serious lung ailment marked by significant inflammation and damage in the alveoli and capillaries of the lungs. Recent research suggests a strong correlation between the onset and advancement of ARDS and an imbalance in the gut microbiota (GM).In this investigation, Mendelian randomization (MR) analysis was utilized, drawing on data from publicly accessible genome-wide association studies. The primary focus was on examining the interplay between GM, inflammatory factors (IFs) and ARDS. Instrumental variables were established through genetic modifications of GM and IFs. Various statistical analysis methods including the inverse-variance weighted model, MR-Egger method and Wald ratio test were applied for comprehensive data analysis.: Eight bacterial taxa within the GM demonstrated a potential causal link with development of ARDS. Notably, the phylum Actinobacteria and the genus Intestinibacter exhibited a negative association with the risk of ARDS. However, Erysipelotrichales (id. 2148), Victivallis (id. 2256), Ruminococcaceae UCG014 (id. 11371), Eubacterium ruminantium group (id. 11340), Erysipelotrichaceae (id. 2149) and Erysipelotrichia (id. 2147) demonstrated a positive association with ARDS risk. Additionally, the study identified a potential causal relationship between the inflammatory factors interleukin-16 and C-C motif chemokine 3 with the occurrence of ARDS.This study strongly suggests that the interaction between gut microbiota (GM) and inflammatory factors (IFs) significantly contributes to the pathogenesis of acute respiratory distress syndrome (ARDS). This underscores their crucial involvement in both the initiation and advancement of this severe lung disorder.